A Comparative Corpus-based Analysis of English Near-synonymous Verbs: inform, notify, impart - Jirawattanasomkul, Siriluk; Punkasirikul, Piyaporn; Parinyaphon, Kerkkrai; Wannathong, Nawaphorn (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2025)
While inform, notify, and impart share core meanings, their semantic nuances and grammatical patterns vary, creating challenges for language learners and professionals. Previous research has primarily relied on dictionary definitions, lacking corpus-based validation to capture real-world usage and contextual distinctions. Addressing this gap, this study integrated corpus linguistics and lexical analysis to examine these verbs in authentic discourse. Using 300 concordance lines per verb from COCA, the study analyzed grammatical patterns, collocations, and frequency distribution alongside dictionary data. Inter-rater reliability ensured semantic classification accuracy, while the Mutual Information (MI) score measured collocational strength. Findings revealed discrepancies between dictionary patterns and real-world usage, with notify commonly used in formal, obligatory contexts, whereas impart frequently appeared in literary and academic discourse. Additionally, corpus data indicated that some dictionary-listed structures, such as inform + reflexive pronoun, were rarely used in contemporary English. These findings underscore the importance of corpus-driven instruction, emphasizing collocation-based learning and professional discourse awareness. Educators should prioritize high-frequency structures and context-based verb usage to enhance accuracy and fluency, contributing to curriculum development, second-language acquisition, and professional training.